Descriptions of two new species of Euxoa Hübner, [1821], subgenus Pleonectopoda Grote, 1873, from Siberia (Lepidoptera, Noctuidae) - Kononenko, V.s.; Behounek, G.; Gyulai, P. (Zootaxa, 2018)
Two new species of the the genus Euxoa Hübner, [1821] (subgenus Pleonectopoda Grote, 1873), Euxoa steideli sp. n. and Euxoa kodara sp. n. are described from the mountains of South and East Siberia. The new species belong to the Holarctic Euxoa westermanii species-group, which is represented in both the New and Old World mainly by alpine and subarctic species. The Palaearctic species of the Euxoa westermanii species-group are reviewed. The placement of Euxoa culminicola (Staudinger, 1870) in the subgenus Pleonectopoda is fixed. New data on distribution of E. (P.) churchillensis (McDunnough, 1932) in the Palaearctic from Chukchi Autonomy are presented. An annotated checklist list of the Palaearctic species of Pleonectopoda (Euxoa, Lepidoptera, Noctuidae, Noctuinae: Noctuini) is presented.